ANALISIS PENERIMAAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH PADA BAPEDA (BADAN PENDAPATAN DAERAH) KABUPATEN GORONTALO - Lantowa, Felmi; Iyonu, Mentari Ariesta (Program Studi Akuntansi, 2023)
One source of local revenue (PAD) is restaurant tax. This is in accordance with law number 28 of 2009 article 11 which states that the restaurant tax rate is set at a maximum of 10%. In general, the function of local taxes is used for the public interest and mostly for the prosperity of society. The aim of this research is to analyze restaurant tax revenues against local revenue at the Gorontalo district regional revenue agency. The research results show that there was a spike or realized restaurant tax revenue in 2017-2019, but in 2020-2022 there was a decline in regional tax revenue. This is partly caused by inaccuracies in taxpayer reporting.